(untitled) (International Journal of Health, Animal Science and Food Safety, 2016)
Ticks can harbor complex and highly variable microbial communities. Among these microorganisms, there are important pathogens of humans and animals that can be transmitted through the blood meal. Less is known about the other members of the microbial community of Ixodida, those that do not cause overt diseases. Among these, Midichloria mitochondrii, symbiont of the tick Ixodes ricinus, is the first described member of the family Midichloriaceae, order Rickettsiales. This bacterium is present in 100% females and is vertically transmitted (Sassera, 2008). The possibility of horizontal transmission is suggested by serological and molecular analyses showing positivity of mammalian blood and sera to M. mitochondrii (Mariconti, 2012; Bazzocchi, 2013). However, its role is still unknown. Recent reports are expanding the view of this family, now including bacteria of great biological and medical interest, indicating a widespread distribution with an increasing range of hosts, with ticks being strongly represented (Epis, 2008). Here we present a molecular screening of 17 tick species (for a total of 92 individuals), detecting and quantifying bacteria closely related to M. mitochondrii in seven of them, including the first report of a midichloriacea in a soft tick species, Ornithodoros maritimus. Based on sequence identity and phylogenetic analysis we propose that these bacteria could constitute the genus Midichloria. The performed screening highlights different prevalence levels in different tick species including one, Ixodes aulacodi, where the bacteria is present in all examined individuals, like in I. ricinus. This result prompts us to hypothesize different roles of Midichloria bacteria in different tick species.